How Can the Functioning of Treatment Wetlands be Enhanced? - Dordio, Ana (2013)
Wetlands have already been recognized to hold the capacity for efficiently reducing or removing large amounts of pollutants from point sources (e.g. municipal and certain industrial effluents) as well as non-point sources (e.g. mining, agricultural and urban runoff) including organic matter, suspended solids, excess of nutrients, pathogens, metals and other micropollutants. This pollutants removal is accomplished by the interdependent action of several physical, chemical and biological processes which include sedimentation, filtration, chemical precipitation, sorption, biodegradation, and plants uptake among others. The mechanisms and the interdependences among the wetlands’ components (water, substrate and biota) are complex and not yet entirely understood, although some progresses have been achieved in the latest years as the awareness to the water depurative functions of wetlands becomes more widespread. In fact, studies have led to both a greater understanding of the potential of natural wetland ecosystems for pollutants assimilation and the design of new natural water treatment systems inspired in these natural systems, the constructed wetlands systems (CWS). These CWS can be defined as man-made systems that have been designed and constructed to utilize the natural processes involving wetland vegetation, soils, and their associated microbial populations to assist in treating wastewater. They are designed to take advantage of many of the same processes that occur in natural wetlands, but do so within a more controlled environment. However, until now these systems have been approached primarily as a “black-box”, without a thorough understanding of the processes involved. Ultimately, the optimization of CWS for the removal of more specific target compounds requires a basic knowledge of the processes involved in the removal of the pollutants and the interactions between those and the CWS components. New trends in CWS research are moving towards the study of such processes and interactions and focus on the selection and optimization of the CWS components for more specific applications. The aim of this work is to present a review on the main pollutant removal and transformation mechanisms in wetlands, the pollutants fate in the system and the roles played by the most important components of CWS (water, substrate and biota) in the processes and how they affect the overall treatment system performance. Some focus will be given to the most recent studies published on this subject especially those involving the treatment of micropollutants by CWS and the mechanisms that may be involved in the removal of these particular substances. Some of the questions remaining to be addressed about the removal mechanisms in CWS and the aspects of CWS operation that still require optimization will also be highlighted in this review.